Pelanggaran Etika Bisnis Islam dalam Transparansi Produk PT. Ajinomoto Indonesia - Aaqilah, Naffa'a; Dara Tsanya Abdul Rohim; Lina Marlina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the violations of Islamic business ethics, particularly in the aspect of product transparency, committed by PT. Ajinomoto Indonesia. The research utilizes a qualitative descriptive method with a literature review approach. Data is collected from various sources, including academic journals, reports, and documented cases related to PT. Ajinomoto Indonesia’s halal issues and product safety. The findings reveal that PT. Ajinomoto Indonesia violated the principles of Islamic business ethics in 2001 by using pork-derived enzymes in MSG production without clear disclosure, which led to its product being declared non-halal by the Indonesian Ulema Council (MUI). Additionally, the company was accused of using harmful additives such as formalin. These practices conflicted with the halalan thayyiban concept in Islam, which demands both lawful and wholesome consumption. This research emphasizes the importance of applying Islamic ethical principles, especially transparency, in the food industry to maintain consumer trust and comply with religious and safety standards. The findings can be used as a reference for policy recommendations in strengthening halal certification governance and ethical auditing. This study provides a focused ethical analysis of a real-world business case from an Islamic perspective, highlighting the consequences of ethical breaches in a Muslim-majority market.